A mathematical model for heating and evaporation of a multi-component liquid film. (February 2018) - Sazhin, S.S.; Rybdylova, O.; Crua, C.
Highlights: A new mathematical model for heating and evaporation of a liquid film. Analytical solutions to heat and mass transfer equations for a liquid film. Validation of the model against experimental data. Abstract: A new model for heating and evaporation of a multi-component liquid film, based on the analytical solutions to the heat transfer and species diffusion equations inside the film, is suggested. The Dirichlet boundary condition is used at the wall and the Robin boundary condition is used at the film surface for the heat transfer equation. For the species diffusion equations, the Neumann boundary conditions are used at the wall, and Robin boundary conditions are used at the film surface. The convective heat transfer coefficient is assumed to be constant and the convective mass transfer coefficient is inferred from the Chilton-Colburn analogy. The model is validated using the previously published experimental data for heating and evaporation of a film composed of mixtures of isooctane/3-methylpentane (3MP). Also, it is applied to the analysis of heating and evaporation of a film composed of a 50%/50% mixture of heptane and hexadecane in Diesel engine-like conditions.